Adversity Quotient and Career Maturity among Undergraduate Students during the Covid-19 Pandemic - Nahwa Adiba; Fitri Ayu Kusumaningrum (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The Covid-19 pandemic has several negative impacts for undergraduate students, namely confusion in choosing a career and low career maturity. This study aims to determine the relationship between adversity quotient and career maturity among undergraduate students during the Covid-19 pandemic. The number of respondents in this study were 120 active undergraduate students aged 18-23 years across all semester levels at universities on the island of Java. There are 33 male students and 87 female students. This research uses a quantitative (correlational) research design. The sampling technique of this research is convenience sampling. The instrument measurements used in this research were Career Maturity Inventory Screening Form S (α = 0.709) and Adversity Quotient Scale (α = 0.761). The results of this study explained that there was a significant positive relationship between adversity quotient and career maturity in undergraduate students. The correlation coefficient value obtained was r = 0.283 and p = 0.001 (p < 0.05). This indicates that there is a significant positive relationship indicated by the strength of the weak relationship between the adversity quotient and undergraduate student career maturity during the Covid-19 pandemic, so there are still other factors that have not been tested yet in this study that may play a more role in increasing career maturity. Based on the results of the study, it can be concluded that the research hypothesis is accepted. Intercorrelation data analysis between aspects, different tests, and demographic correlation tests (gender, semester level, internship/training experience, and parents' career direction) will be discussed further.